P061 Continuous thetaburst stimulation for the treatment of refractory epilepsy – Case report. Issue 3 (March 2017) - Carrette, S.; Klooster, D.; Nollet, L.; Duprat, R.; Staljanssens, W.; Van Mierlo, P.; Van Dycke, A.; Carrette, E.; Raedt, R.; Meurs, A.; Baeken, C.; Vonck, K.; et al.
Abstract : Introduction: Thetaburst stimulation (TBS) is a repetitive transcranial magnetic stimulation (rTMS) protocol that may induce long lasting neuroplasticity. Continuous TBS (cTBS), a cortical excitability reducing protocol, would be the stimulation protocol of choice for the treatment of epilepsy. The lower stimulation intensity and number of pulses compared to conventional rTMS may imply superiority with regards to safety, tolerability and applicability in the clinic. Methods: Two patients with refractory focal epilepsy due to a low-grade tumor in the rolandic area were treated with cTBS and followed-up for effect on seizure frequency and adverse effects. The stimulation protocol consisted of 5 spaced cTBS trains (600 pulses/train, 80% resting motor threshold) during 4 consecutive days delivered over the ictal onset zone using online neuronavigation. Seizure frequency was assessed over a 4 week baseline period, a 1 week treatment period and an 8 week follow-up period. Results: Patient 1 suffered from simple partial motor seizures (SPS), often leading to falls and post-ictal paresis, and myoclonic seizures of the left leg. During baseline 3 SPS and 12 myoclonic seizures occurred. In the first week following cTBS, the patient solely experienced isolated auras consisting of a descending sensation towards the left leg. No SPS occurred. Thereafter, overall SPS frequency was unchanged during follow-up, but the patient reported diminished seizure severity with regards to duration, jerking and paresis. This gradually returned to baseline during follow-up. Notably, myoclonic seizures were completely suppressed for a duration of 6 weeks. Patient 2 suffered from frequent SPS with jerking of the right truncal muscles, spreading to the right arm, head and less often the right leg. Sixteen SPS occurred during baseline, whereas the patient remained seizure-free throughout the treatment week and 13 days thereafter, for a total of nearly three weeks. Follow-up is ongoing at the moment of this report. Stimulation with cTBS was well-tolerated and did not induce adverse effects in either of the patients. Conclusion: This case report describes safety and potential anti-epileptic effects of cTBS. Both patients experienced a period of diminished seizure frequency, for a duration of 3–6 weeks following a cTBS treatment protocol.